A Study of Health-Related Characteristics in the Elderly in Kon Tum City - Le , Huu Loi; Doan Thi Tuan, Hoang Thi Thuan, Huynh Thuy Lan Huong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
Background: Population aging in the context of low social and economic development is a huge challenge because the aging population requires more spending on health care, retirement, and pensions. According to a study in Hanoi, 65% of older people rated themselves unwell and 35% rated normal health. According to the 2009 Viet Nam Population and Housing Census data, Kon Tum belongs to the group of 8-10% of the elderly population. Health is the most important criterion when analyzing the situation of the well-being of the elderly. Determining the health characteristics of the elderly is essential to help develop programs and policies to improve health care. Objectives: The study aims to determine the general health characteristics and describe some factors related to the health of the elderly in Kon Tum city. Methods: A cross-sectional analysis of 138 elderly persons living in Kon Tum city was conducted. Inclusion criteria were elderly aged between 60 and 80 years, absence of confusion (i.e., no cognitive or behavioral problems), and informed consent to participate in the study. Results: The prevalence of hypertension in the elderly was 46.04%. Heart rate of 60-100 beats/minute was observed in 93.52%. Thin weight was 10.08%, while overweight and obesity accounted for 48.2%. Alcohol use was 21.58%, and tobacco use was 14.39%. Vision loss was reported in 92.09%, hearing abnormalities in 9.35%, anemia in 5.04%, hyperglycemia in 48.2%, and lipid disorders in 87.05%. The prevalence of risks included a risk of falling (9.35%), frailty (10.07%), pre-frailty syndrome (60.43%), malnutrition (65.47%), dependency (8.63%), depression (36.69%), and cognitive impairment (49.64%). Conclusion: Attention is needed for diseases in elderly persons, including anemia, hyperglycemia, and lipid disorders, as well as the risks of falling, frailty, malnutrition, dependency, depression, and cognitive impairment among the elderly in Kon Tum City.